Wave observation in the marginal ice zone with the TerraSAR-X satellite - Gebhardt, Claus P.; Bidlot, Jean-Raymond; Gemmrich, Johannes; Lehner, Susanne; Rosenthal, Wolfgang; Pleskachevsky, Andrey (Ocean Dynamics, 2016)
This article investigates the penetration of ocean waves into the marginal ice zone (MIZ), observed by satellite, and likewise provides a basis for the future cross-validation of respective models. To this end, synthetic aperture radar images from the TerraSAR-X satellite (TS-X) and numerical simulations of the European Centre for Medium-Range Weather Forecasts (ECMWF) are used. The focus is an event of swell waves, developed during a storm passage in the Atlantic, penetrating deeply into the MIZ off the coast of Eastern Greenland in February 2013. The TS-X scene which is the basis for this investigation extends from the ice-free open ocean to solid ice. The variation of the peak wavelength is analysed and potential sources of variability are discussed. We find an increase in wavelength which is consistent with the spatial dispersion of deep water waves, even within the ice-covered region.